Economy in fertilizer use in maize (Zea mays)-wheat (Triticum aestivum) sequence under rainfed condition in Himchal Pradesh - RAMESHWAR, RAMESHWAR; SINGH, C M (The Indian Journal of Agricultural Sciences, 2013)
A Held study was conducted for 3 years during rainy season (kharif) 1993-94 to winter season (rabi) 1995-96 under mid-hill conditions of Himachal Pradesh to determine the appropriate combination of fertilizer scheduling along with appropriate time of farmyard manure application. The cumulative application of farmyard manure to both maize ( Zea mays L.)and wheat (Triticum aestivum L. emend. Fiori & Paul.)crops @ 10 tonnes/ha in each season gave significantly higher grain yield, followed by farmyard manure applied directly,and the lowest yield with its residual effect in both maize and wheat crops. Although during the first year both the crops responded to N120 P6040 in maize and N80 P40 K40 in wheat, during the second and third years the crops responded to N90 P45 K30 in maize and N60 P30 K30 in wheat. There is possibility of economizing fertilizer by 25% of NPK in both maize and wheat under rainfed condition without compromising with grain-yield production.